A scoping review of end-of-life discussions and palliative care: implications for neurological intensive care among Latinos in the U.S. - Monica M. Diaz; Lesley A. Guareña; Bettsie Garcia; Christoper A. Alarcon-Ruiz; Stella M. Seal; Clio Rubinos; Dulce M. Cruz-Oliver; J. Ricardo Carhuapoma (Elsevier, 2024)
Summary: Goals of care (Goals-of-care) discussions and palliative care (PC) are crucial to providing comprehensive healthcare, particularly for acute neurological conditions requiring admission to a neurological intensive care unit. We identified gaps in the literature and describe insight for future research on end-of-life discussions and PC for U.S. Latinos with acute neurological conditions. We searched 10 databases including peer-reviewed abstracts and manuscripts of hospitalized U.S. Latinos with acute neurological and non-neurological conditions. We included 44 of 3231 publications and identified various themes: PC utilization, pre-established advanced directives in Goals-of-care discussions, Goals-of-care discussion outcomes, tracheostomy or percutaneous gastrostomy tube placement rates among hospitalized Latinos. Our review highlights that Latinos appear to have lower palliative care utilization compared with non-Latino Whites and may be less likely to have pre-established advanced directives, more likely to have gastrostomy or tracheostomy placement and less likely to have do-not-resuscitate status.